Closed Form Solution of Synchronous Machine Short Circuit Transients - Gibson H.M. Sianipar (Journal of Engineering and Technological Sciences, 2010)
This  paper  presents  the  closed  form  solution   of  the  synchronous machine  transients undergoing short circuit. That analytic formulation has been derived  based  on  linearity  and  balanced  conditions  of  the  fault.  Even  though restrictive, the proposed method will serve somehow or other as a new resource for  EMTP  productivity.  Indisputably  superior, the  closed-form  formulation has some  features  inimitable  by  discretization  such  as  continuity,  accuracy  and absolute numerical stability. Moreover, it enables us to calculate states at one specific  instant  independent  of  previous  states  or  a  snapshot,  which  any discretization methods cannot do.